Pentingnya Budaya Strategis Dalam Studi Hubungan Internasional - Al Ariqi, M Afifuddin; Fauzi Ilham, Muhammad (Philosophiamundi, 2023)
This research aims to investigate the importance of strategic culture in the context of International Relations studies with a focus on its influence on a country's decision-making, foreign policy and security strategy. Through a descriptive qualitative approach with a library research method, this study analyzes information from various text sources to identify the role of strategic culture in the dynamics of interstate relations. The analysis covers the evolution of the concept of strategic culture, from historical perspectives to the post-Cold War paradigm shift. In addition, it explains the role of political culture and how the development of strategic culture relates to the changing international landscape. The results highlight the importance of strategic culture in decision-making processes, foreign policy formation, and security strategy, while addressing current debates regarding cultural determinism and the ability of culture to adapt.